Gender and Ethnicity in Social Studies Textbooks: Unveiling Bias in Educational Narratives - Erna Mena Niman (Universitas Pendidikan Ganesha, 2025)
Social Studies textbooks within local cultural contexts often fail to adequately represent the diversity of knowledge, traditions, and social practices, which may limit students’ connection to their own cultural identities. This issue is important to examine because textbooks play a strategic role in shaping students’ social understanding, values, and perspectives. This study aims to analyze and explore gender and ethnic representations in elementary Social Studies textbooks and to identify forms of bias embedded within the content. This research employed a qualitative approach, with the research subject consisting of Social Studies textbooks used at the elementary school level. Data were collected through document analysis, using content analysis guidelines and discourse analysis frameworks as research instruments. Data analysis was conducted using content analysis to identify patterns, themes, and the frequency of gender and ethnic representations, as well as critical discourse analysis to examine how language constructs meaning, identity, and power relations. The findings reveal a dominance of male representation in leadership and innovation roles, while female characters are more frequently portrayed in domestic roles. In addition, ethnic minority groups tend to be marginalized within historical and social narratives. These results indicate that the language and narrative structures of the textbooks continue to reproduce social biases that shape students’ perceptions of gender and ethnic roles. Therefore, this study concludes that curriculum revision and the development of more inclusive, equitable, and representative Social Studies textbooks are necessary to support education that is sensitive to social and cultural diversity.